Musical Opera Theatre Of Siak Dengan Penerapan Prinsip Desain Renzo Piano - Fadhil, Iman; Faisal, Gun; Aldy, Pedia (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Siak Sri Indrapura is a city rich in diversity of tradition, arts and traditional knowledge, this can be seen from the attractiveness of local traditions that have the potential as tourist attractions and also plays a major role in executing arts events and performances in Riau Province. Musical Opera Theater of Siak is a place for art activities with cultural values that also functions as a space for interaction of community and information activities, so it will support the development of community interests and talents in performing arts. By using Renzo Piano’s design principles, it is able to create a connection between performing arts through architecture and the use of surrounding environment and culture in the city of Siak. With Audiosonic Wave as the concept and being transformed by Renzo Piano’s design principle, this building has architectural qualities that can enhance creativity and ideas about performing arts through architectural elements. Keyword: Musical Opera Theatre, Art